Surface temperature distribution in a composite brake rotor - Adebisi, Adetayo A.; Maleque, Md. Abdul; Shah, Qasim Hussain (Universiti Malaya, 2011)
The prediction of surface temperature for brake rotor is regarded as an important step in studying the brake system performance. The frictional heat generated on the rotor surface can influence excessive temperature rise which in turn leads to undesirable effects such as thermal elastic instability (TEI), premature wear, brake fluid vaporization (BFV) and thermally excited vibrations (TEV). The purpose of this study is to investigate the temperature distribution profile for brake caliper pressure application of 0.5, 0.10, 1.5 and 2.0 MPa with a speed of 60km/h braking condition on the disc rotor surface. The brake rotor assembly is built by using a 3 dimensional finite element model of a real car brake rotor. To verify the simulation results, an experimental investigation is carried out. It is believed from the study that composite brake rotor influences the temperature distribution and heat dissipation rate which could prevent excessive temperature rise and subsequently prolong the service life of the rotor. The finite element method is cost effective and also assists the automotive industry in producing optimised an